Efektifitas Manajemen Kesiswaan Melalui OSIM dalam Membentuk Karakter Disiplin Siswi - Ningsih, Rahma Wati; Hamid, Abdul; Ghufron, Ghufron (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
This research aims to describe and analyze student management through osim in shaping the disciplined character of female students which was carried out at Madrasah Diniyah Darul Lughah Wal Karomah Kraksaan Probolinggo, East Java. This research is a qualitative descriptive study. This method is a type of research that describes aspects that form the context of the research. Monitor and present the actual situation that occurs in the field regarding student management at Madrasah Diniyah. The data analysis process is carried out by collecting data and simplifying it according to needs so that it becomes important points in the research, then the researcher analyzes the data by discarding data that is not needed. This research obtained data directly from the research subjects, namely the head of Madrasah Diniyah, head of Madin student affairs, and head of Osim. In the form of interview results, seeing the situation directly (observation), and documentation. The results of the research show that student management through osim is very effective in shaping the disciplined character of Madrasah Diniyah Darullughah Wal Karomah students. By carrying out routine planning, implementation and evaluation.